2019
DOI: 10.1002/jctb.5971
|View full text |Cite
|
Sign up to set email alerts
|

Juice from fescue grain sorghum to produce bioethanol for gasoline additive

Abstract: BACKGROUND: The purpose of this study was to evaluate the juice of the fescue grain sorghum, since it is a low-cost agricultural waste, for the production of bioethanol to be used as a gasoline additive. In addition, the octane number has been investigated by varying the ethanol-gasoline mixture 2, 6 and 10%. RESULTS:The wort fermentation was carried out with commercial bread yeast (Saccharomyces cerevisiae). The liquor obtained was characterized and quantified through gas chromatography. Bioethanol-gasoline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Liu in 2020 31 used different energy sources to study energy research on grains drying, and found that the heat conversion rate of barn ABF hot blast stoves reached more than 90%, which has the characteristics of high efficiency, energy saving, and environmental protection. Studies have shown that ABF has a higher octane value and a higher anti-knock performance, which is an excellent additive to improve the octane value of gasoline 19 , 39 , 40 . However, ABF also has the characteristics of low calorific value, which is only 60% of some high-calorific value fuels, it is sufficient for TC, but for other curing that requires higher calorific value, it is necessary to increase the calorific value of ABF.…”
Section: Discussionmentioning
confidence: 99%
“…Liu in 2020 31 used different energy sources to study energy research on grains drying, and found that the heat conversion rate of barn ABF hot blast stoves reached more than 90%, which has the characteristics of high efficiency, energy saving, and environmental protection. Studies have shown that ABF has a higher octane value and a higher anti-knock performance, which is an excellent additive to improve the octane value of gasoline 19 , 39 , 40 . However, ABF also has the characteristics of low calorific value, which is only 60% of some high-calorific value fuels, it is sufficient for TC, but for other curing that requires higher calorific value, it is necessary to increase the calorific value of ABF.…”
Section: Discussionmentioning
confidence: 99%
“…In this In Focus edition of the Materials and the Environment Symposium , 11 articles were selected for publication among all the amazing work that was presented during this event. This In Focus includes articles on the production of photocatalysts for the degradation of pollutants such as herbicides, as well as the use of sugar cane bagasse and coal fly ash for the production of adsorbent materials, and the production of materials with enhanced water adsorption for agricultural applications.…”
mentioning
confidence: 99%